2020
DOI: 10.1038/s41598-020-59086-0
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Leadership Characteristics from Social Media Data during Natural Hazards using Personality Traits

Abstract: With the availability of smart devices and affordable data plans, social media platforms have become the primary source of information dissemination across geographically dispersed users/locations. it has shown great potential across different application domains including event detection, opinion analysis, recommendation, and prediction. However, the process of extracting useful information from the collected voluminous social media data during natural hazards is a standing problem that needs significant atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…In addition, the personality traits, except for neuroticism, of public health organizations’ Instagram accounts were predicted from the photo features with an acceptable level of accuracy. Given that the personality of individual users was shown to be predictable from their photo features [ 15 , 34 ], this result can be meaningful in that organizational accounts in social media can be investigated from the perspective of personality which has been employed for examining individual users’ accounts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the personality traits, except for neuroticism, of public health organizations’ Instagram accounts were predicted from the photo features with an acceptable level of accuracy. Given that the personality of individual users was shown to be predictable from their photo features [ 15 , 34 ], this result can be meaningful in that organizational accounts in social media can be investigated from the perspective of personality which has been employed for examining individual users’ accounts.…”
Section: Discussionmentioning
confidence: 99%
“…Their results indicated that extraversion, emotional stability, and agreeableness were positively associated with cost efficiency and profitability, while conscientiousness were negatively associated with them. Agarwal and Toshniwal [ 34 ] analyzed tweets under various natural hazards conditions and found that Twitter users with a higher level of extraversion and agreeableness uploaded more tweets of leadership concerning behaviors under crisis situations.…”
Section: Related Workmentioning
confidence: 99%
“…The results of the study are in the form of useful insights that the characteristics of the leadership are influenced by hazard, domain, and user centrality. The results are important for assessing the quality of prospective leaders based on their characteristics [22].…”
Section: Related Workmentioning
confidence: 99%
“…In other words, they refer to individuals whose opinions influence others’ decision to choose or abandon a particular thing. The source of information reaches these leaders, who then deliver it through messages (Agarwal and Toshniwal, 2020) to their social groups (Kaufmann et al , 2012) such as international students who mostly seek university information through online and social media platforms (Beech, 2015; Bukhari et al , 2020). Furthermore, individuals with strong personalities are more associated socially and likely to impact the opinions of others in a small group circle (Broeder and van Hout, 2019), including students, family and friends (Morrish and Lee, 2011).…”
Section: The Influence Of Opinion Leaders On Students’ Intention To S...mentioning
confidence: 99%